Efektivitas Program Pendidikan Lanjut Usia Terhadap Kualitas Hidup Lansia di Komunitas : A LITERATUR REVIEW - Ainun Jariah; Kusbaryanto Kusbaryanto (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Background: The elderly education program is a long-term learning model aimed at the elderly to improve their knowledge, especially regarding health. Education and learning are considered to be important factors in facilitating participation in society and enabling older people to enjoy positive quality of life as they age. By actively participating in this activity can improve the quality of life in the elderly. Objective: To determine the effectiveness of the elderly education program on improving the quality of life in the elderly. Method: The method of writing this study with a literature review and using the Google Scholar, Pubmed, Science Direct database, using Keywords: